Building Bridges: Development Collaboration Between Radiology, Nursing, And Pharmacy Departments. A New Appraisal (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the crucial collaboration between radiology nurses and pharmacists in ensuring optimal patient care within the radiology department. It highlights key areas where their teamwork enhances procedures. Collaboration allows for the development of clear and comprehensive educational materials for patients regarding medications used in radiology procedures. Safe Contrast Media Handling: Established protocols ensure safe administration through collaboration. Pharmacists contribute by ensuring proper storage, handling, and disposal of contrast media. The Future of Radiology: The article explores how automation might impact their roles and emphasizes the continued importance of collaboration in optimizing workflow and patient safety. Case studies showcase how successful collaboration between radiology nurses and pharmacists has led to positive patient outcomes. By working together, these healthcare professionals significantly contribute to safe, effective, and patient-centered care in radiology.